Consumptive Behavior in Adolescents and Its Impact on Financial Management: Case Studies and Practical Implications - Priyo Sasmito; Ari Riswanto; Fazrian Thursina; Fitriana Kusuma; Riffalni Dela Nurlaila (Westscience Press, 2023)
Consumptive behavior in adolescents has become the focus of attention in the context of financial management. This article aims to analyze consumptive behavior in adolescents and its impact on their financial management using a quantitative approach. Through a quantitative survey involving a sample of adolescents, this study aims to identify influencing factors that influence consumptive behavior and analyze the short-term and long-term impact of consumptive behavior on adolescent financial management. The research method used is a quantitative survey with a structured questionnaire. The study sample consisted of adolescents aged 15-18 years who were randomly selected from several schools in certain areas. The questionnaire included questions about spending patterns, consumption motivation, financial management, and financial knowledge of adolescents. The collected data were analyzed using descriptive statistical techniques and regression analysis to identify the relationship between consumptive behavior and financial management. The survey results show that influencing factors such as marketing, social media, peers, and psychological factors play an important role in adolescent consumptive behavior. In addition, excessive consumptive behavior has a negative impact on adolescent financial management, including consumptive debt problems, difficulty saving, and lack of financial knowledge. The long-term impact of this consumptive behavior can lead to financial risks in the future.